Reducing complications in post-bariatric plastic surgery: our experience and literature review - Romano, Lucia; Zoccali, Giovanni; Orsini, Gino; Giuliani, Maurizio (Acta Biomedica Atenei Parmensis, 2019)
Summary. Background: With the rise in obesity, there has been a similar increase in bariatric surgery. This resulted in numerous patients losing significant weight with accompanying circumferential body contouring issues. This has led to an amazing increase in the number of body contouring procedures performed. Methods: The aim of this work is to revise the cases of body contouring in 78 ex-obese patients who underwent body contouring surgery in the Department of Health Life and Environmental Sciences – Plastic Reconstructive and Aesthetic Plastic Surgery Section, from 2007 to 2016. Results: The authors have noticed a deep relationship between adverse events and cigarette smoking and with pre-operative BMI. Regardless of these variables, the authors focused on the protocol for the management of patients, which required a collaboration between medical and nursing staff. Conclusions: Ex-obese patients have an important risk for complications, but the comparison of our personal data with those of the international literature confirms the efficacy of our management protocol with regard to the prevention of complications. (www.actabiomedica.it)